Cutaneous Adverse Drug Reactions in a Tertiary Care Teaching Hospital in India: An Intensive Monitoring Study - Thakkar, Sejal (Indian J Dermatol, 2017)
BACKGROUND: The epidemiological data based on intensive monitoring studies are limited for the cutaneous adverse drug reactions (CADRs) in terms of incidence. Most of earlier Indian studies focused only on types and causative drugs of CADRs. AIM: The aim of this study is to analyze the CADRs with reference to the incidence, its subgroup analysis, causative drugs, and other clinical characteristics in Indian population. METHODOLOGY: Intensive monitoring study was carried out over a period of 3 years in the dermatology outpatient and inpatient department. CADRs due to only systematically administered drugs were considered. The WHO definition for CADR, the WHO causality definitions, modified Schumock and Thornton's criteria for preventability, and International Conference on Harmonisation E2A guidelines for seriousness were considered. Incidence was expressed in percentage and its 95% confidence interval. The incidence was analyzed on basis of characteristics of study population and CADRs. RESULTS: A total of 171 CADRs were observed from 37,623 patients. The CADR incidence was 0.45% (95% CI: 0.39–0.53). The incidence did not significantly differ in different age groups and gender. Commonly observed CADRs were maculopapular rash (23.98%), urticaria (21.64%), and fixed drug eruptions (FDEs) (18.13%). Antimicrobials (35.18%) and nonsteroidal anti-inflammatory drugs (NSAIDs) were suspected in all common CADRs. Anti-infective and NSAIDs were most commonly suspected drugs in overall CADRs, maculopapular rash, urticaria, FDEs, and erythema multiforme. The exact nature of drugs remained inaccessible in one-fourth cases due to use of the over-the-counter self-medications. The incidence of preventable and serious and fatal CADRs was 0.08% (95% CI: 0.05–0.11), 0.04% (95% CI: 0.02–0.06), and 0.003% (95% CI: 0.000–0.001), respectively. CONCLUSION: Ethnic characteristics should be considered while interpreting incidence from the international studies. The demographic characteristics of study population do not affect the incidence of CADRs. Indian patients should be sensitized about hazards of self-medications.